Quality Assessment of Ecoprinted Tablecloths Using Avocado Leaves with Tunjung and Limestone Mordants - Arlina Lilayanti; Adhi Kusumastuti (Jurnal Penelitian Pendidikan, 2026)
This study aims to determine the quality of avocado leaf ecoprint results using tunjung and limestone mordants on tablecloths. This study uses an experimental method with a quantitative approach. The object of the study is primissima cotton fabric processed into a tablecloth with an avocado leaf ecoprint motif. The independent variable in this study is the type of mordant, namely tunjung and limestone, while the dependent variable is the visual quality of the ecoprint results which is focused on the clarity of the motif and the appearance of the colour. Data collection was carried out through organoleptic tests by three expert panellists using a rating scale of 1-5. Data were analysed descriptively in the form of percentages. The results showed that the limestone mordant obtained a percentage value of 34.44% with a less category, while the tunjung mordant obtained a percentage value of 55.56% with a sufficient category. These findings indicate that the tunjung mordant produces better visual quality ecoprint compared to limestone, especially in terms of clarity of motif and colour intensity. Thus, the type of mordant makes a difference in the quality of the avocado leaf ecoprint results, and the tunjung mordant is more recommended for producing more optimal ecoprint tablecloth products.